Effects of High Food Prices on Non-Cash Food Subsidies (BPNT) in Indonesia - Case Study in East Nusa Tenggara - Assyifa Szami Ilman (Center for Indonesian Policy Studies (CIPS), 2020)
Indonesians living in poverty spend the majority of their income on food on often inadequate food consumption. The Non-Cash Food Subsidy (BPNT), a social program to support low income families with food spending has helped alleviate this burden. However, this paper shows that high food prices will impair the positive impacts of BNPT, based on conducted experiments with mothers in West Sumba and Southwest Sumba districts, East Nusa Tenggara. We outline two policy recommendations: maintain the BPNT Program & reform food policies that undermine the purpose and effectiveness of the Program.
Keywords: 330; Non-Cash Food Subsidies; Food prices in Indonesia; rice; eggs; sumba; east nusa tenggara; e-warong; e warong; kube; PKH; ilman